2010
DOI: 10.1021/nn9014449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fabrication Parameters on Three-Dimensional Nanostructures of Bulk Heterojunctions Imaged by High-Resolution Scanning ToF-SIMS

Abstract: Solution processable fullerene and copolymer bulk heterojunctions are widely used as the active layers of solar cells. In this work, scanning time-of-flight secondary ion mass spectrometry (ToF-SIMS) is used to examine the distribution of [6,6]phenyl-C61-butyric acid methyl ester (PCBM) and regio-regular poly(3-hexylthiophene) (rrP3HT) that forms the bulk heterojunction. The planar phase separation of P3HT:PCBM is observed by ToF-SIMS imaging. The depth profile of the fragment distribution that reflects the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 37 publications
2
55
0
Order By: Relevance
“…Co‐sputtering with a 10 kV C 60 + and a 0.2 kV Ar + beam is known to preserve the chemical structure of the remaining surface for various organic/polymeric materials . Using the co‐sputtering beam as the ionization source, molecular D‐SIMS spectra were also acquired (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Co‐sputtering with a 10 kV C 60 + and a 0.2 kV Ar + beam is known to preserve the chemical structure of the remaining surface for various organic/polymeric materials . Using the co‐sputtering beam as the ionization source, molecular D‐SIMS spectra were also acquired (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The apparatus is based on a PHI 5000 VersaProbe (ULVAC‐PHI, Chigasaki, Japan) scanning X‐ray microprobe system operated at a base pressure of <1 × 10 –7 Pa, which was achieved by evacuation using ion getter pumps. The Ar + ion source was operated at 0.2 kV and 300 nA (measured on an Au target) using a floating voltage of 500 V. A voltage setting of 0.2 kV has been previously found to preserve the chemical structure of the remaining surface for various organic/polymeric materials while yielding a more stable sputtering rate . The ray path contained a 1° bend to filter fast Ar atoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, ToF‐SIMS equipped with in situ cluster ion sputtering, was used to study the depth‐dependent distribution of molecules in organic light‐emitting diodes (OLEDs) and their degradation mechanisms. In combination with the high lateral resolution of the scanning probe microscopy, cluster ion sputtering was also used to construct the 3D images of nanostructures at bulk heterojunctions . Recent studies have shown by using ToF‐SIMS that ion migration could be one of the degradation mechanisms …”
Section: Introductionmentioning
confidence: 99%